Fixed Investment and Economic Growth: ARDL and Causality Exploration for SADC Countries - Mbona, Reginald Masimba; Mumba, Chilombo Stephania; Mangudhla, Tinashe (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In assessing the short run and the long-run effects of fixed investment and economic growth among Southern Africa countries, we evaluated the economic progress of the SADC (Southern African Development Committee) region. Our objective is to determine how variables (GDP, purchasing power parity, inflation, electricity, balance-of-payments, and unemployment) can be affected by the fixed investment. In determining how fixed investment affects economic activities and policies among the states, the ADRL estimation approach is applied. Using data from 13 countries in the SADC region from the period 1992-2018, we enumerate the variables’ marginal returns against the fixed investment component. The results of diagnostic and other tests show that all statistical procedures are robust. The result proves that the benefits of fixed investment are yielded over a long period rather than short periods. As a result, the cost in the short term cannot be compared to the benefits that will be enjoyed later by an economy as it becomes productive. Furthermore, the lack of consistent fixed investment among countries will eventually lead to insufficient cash flow, which will negatively affect the currency. These results would seem to suggest that the introduction of policies that promote investment will massively contribute to increased productivity and positive economic growth in the region.